New Neotropical Saicinae: new species of Buninotus Maldonado Capriles, Caprilesia Gil-Santana, Marques & Costa, and Pseudosaica Blinn (Hemiptera: Reduviidae) - Castro Huertas, Valentina (2022)
Buninotus palikur n. sp. (French Guiana), Caprilesia napuruna n. sp. (Ecuador), Caprilesia sikuani n. sp. (Colombia), and Pseudosaica charrua n. sp. (Argentina) are described. Detailed descriptions of coloration patterns, external morphology and genitalia are offered and discussed for each genus and species. Digital images of external morphological characters and of the genitalia are provided. Updated keys to the species of Buninotus, Caprilesia, and Pseudosaica are presented to facilitate the identification of the species.